Finding a Good Price in Opaque Over-the-Counter Markets - Zhu, Haoxiang (Review of Financial Studies, 2012)
This paper offers a fully rational, dynamic model of opaque over-the-counter markets. An investor searches for an attractive price by visiting multiple dealers in any chosen sequence, including repeat contacts. The dealers do not observe negotiations elsewhere in the market, including the order of contacts. Under stated conditions, a repeat contact with a dealer reveals the investor's reduced outside options and worsens the price quote. When the fundamental value of an asset is uncertain, market opacity and uncertain contact order could exacerbate adverse selection and lead to inefficient market breakdown.